2016
DOI: 10.1039/c6ce02261h
|View full text |Cite
|
Sign up to set email alerts
|

Twist and shout: a surprising synergy between aryl and N-substituents defines the computed charge transport properties in a series of crystalline diketopyrrolopyrroles

Abstract: This version is available at https://strathprints.strath.ac.uk/58791/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 44 publications
1
18
1
Order By: Relevance
“…In all molecules the 4MB group is quasi perpendicular to the DPP plane with dihedral angles of 85.8°, 89.5° and 88.7° for ThDPP, OMePhDPP and ThPhDPP respectively. This interesting conformational feature is also seen for benzyl derivatives, and the methoxy substituent does not alter significantly the orientation of the group. In 4MB ThDPP the thiophene rings are arranged in the anti orientation with the sulfur atoms oriented towards the alkyl chain, which is similar to previously reported dialkyated compounds containing this core .…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…In all molecules the 4MB group is quasi perpendicular to the DPP plane with dihedral angles of 85.8°, 89.5° and 88.7° for ThDPP, OMePhDPP and ThPhDPP respectively. This interesting conformational feature is also seen for benzyl derivatives, and the methoxy substituent does not alter significantly the orientation of the group. In 4MB ThDPP the thiophene rings are arranged in the anti orientation with the sulfur atoms oriented towards the alkyl chain, which is similar to previously reported dialkyated compounds containing this core .…”
Section: Resultsmentioning
confidence: 66%
“…[11] The planar core of these compounds (Figure 1) consists of a π-conjugated dilactam system which can be substituted with different aromatic groups at the 3-and 6-positions, and with alkyl derivatives as the Nsubstituents. [12,13] Thus, the compounds present a multitude of opportunities for structural and electronic modification via synthetic functionalization, such as end capping of the aromatic sections, [14,15] the addition of conjugated flanking units to extend charge delocalization [16,17] and solubilizing chains of varying polarity at the N position to aid processing. [18] This alkylation of DPP derivatives gives rise to solubility in relatively low polarity organic solvents, [19][20][21] as well as solubility in more polar solvents when heteroatom-containing chains are appended.…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with the significantly larger number of phenyl (77) vs thiophene (28) DPP single crystal structures contained in the Cambridge Structural Database (CSD). Contrary to a popular notion that phenyl-substituted DPPs (PDPPs) are not structurally optimal for OFET applications, 15 we have recently demonstrated that phenyl-based DPP architectures represent a theoretically superior alternative to equivalent thiophene and furan-based systems, 16 particularly in crystalline hole transport environments. Via judicious choice of aryl and Nsubstituents, PDPP single crystal structures can exhibit comparable or even greater charge transfer integrals than rubrene, for which mobilities of 20 cm 2 V -1 s -1 have been reported in the crystalline state.…”
Section: Introductionmentioning
confidence: 67%
“…We anticipate that PDPP-based architectures may offer a clear potential for the realization of thermally activated reversal of the charge transfer character. PDPP systems are often undervalued as organic semiconductors on account of reduced planarity when compared to thiophene and furan analogues, 16 despite their comparable computed innersphere reorganization energies at torsional angles often observed in crystalline environments. It was therefore of interest to explore the effects of planarity on the intermolecular interactions and charge transfer integrals for fully eclipsed (Δx/Δy of 0.0/0.0 Å) and twodimensional model global minimum (Δx/Δy of 3.3/0.3 Å) dimer pairs by systematically increasing the dihedral angle of the core phenyl rings with respect to the DPP core.…”
Section: Two-dimensional π-π Dimer Modelmentioning
confidence: 99%
See 1 more Smart Citation